Celestina: Genius and figure in times of transformation: A recreation based on the novel El manuscrito de Piedra by Luis García Jambrina - Conci, Laura Noemí; Muñoz, Lucía Isabel (Revista Melibea, 2024)
The distinctive mark of La Celestina lies in being considered by critics as a book of breakups; It breaks with medieval literary norms and the work is a fundamental link with Modernity. From then on, and until the present, the work knows no geographical limits, and such is its appeal that it has had continuations, adaptations, among many other types of presentations and performances. In this context, and following some lines of research proposed by researchers Jérome François (2015, 2018) and Álvaro Ceballos Viró (2018), it is proposed to analyze the rewriting of the work attributed to Fernando de Rojas in the novel The Stone Manuscript by Luis García Jambrina (2017). For this purpose, the notion of transfictionality will be followed as a phenomenon that is present in García Jambrina's work and establishes modified migratory relationships at the level of the fiction of his novel. In it, for example, Fernando de Rojas and Celestina are transfictional characters, insofar as they shape and modify the original source. García Jambrina's rewriting appropriates La Celestina and offers the reader a new reading and a new look at the already famous Spanish classic. The intertextual experience allows a representation of the masterful medieval work in contemporary projection.